Nutritional Status of Senior Citizens in Selected Rural and Urban Area of Kaski, Nepal - Gautam, S; Shrestha, N; Shah, T; Angur, B (Journal of Gandaki Medical College-Nepal, 2018)
Background: Nutritional status is a valuable determinant of quality of life as well as morbidity and mortality. Adequate nutrition, including balanced diet is important among the senior citizens for maintaining good health. Objectives: To assess the nutritional status of senior citizens, compare between rural and urban and find out association between demographic variables and study parameters.Methods: A community based cross-sectional comparative study was carried out in one Municipality and one VDC of Kaski district, Nepal. Stratified random sampling was adopted to draw 120 samples from urban, 120 from rural. Data was collected by face-to-face interview with the respondents using semi-structured questionnaire. Anthropometric measurement (Height and weight) and hemoglobin measurement was done for assessment of nutritional status.Results: Underweight was found in maximum (47.5%) respondents in rural than urban (18.3%). while overweight was in maximum in urban (30.0%) than in rural (12.5%). Similarly, BMI within normal range was higher in urban (45.8%) than in rural (37.5%). Mean BMI in rural was 19.0 ±4.1 and in urban was 23.2 ±4.7. Below normal hemoglobin level was slightly higher in rural (47.5%) than in urban (44.17%). Mean hemoglobin in rural was 11.89 ±1.63 and urban was 12.06 ±1.27.Conclusions: The study concludes that, underweight was found more among in rural senior citizens but overweight was found more among in urban senior citizens. Below normal hemoglobin level was more among rural samples. There was statistically significant association of mean BMI between rural and urban but not statistically significant association of mean hemoglobin between rural and urban.  J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 46-51